2016
DOI: 10.4238/gmr.15027332
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between PPARg2 gene Pro12Ala polymorphism and cerebral infarction in an Inner Mongolian Han Chinese population

Abstract: ABSTRACT. The variant of PPAR-g2 has been shown to promote the increase of carotid IMT in patients suffering from cerebral infarction and the Pro12Ala polymorphism in the peroxisome proliferatoractivated receptorg2 (PPARg2) gene may be associated with cerebral infarction. However, due to the different genetic background, race, and regional variations of cerebral infarction patient, the results of investigations into this subject differ. The aim of this study was to investigate this polymorphism in relation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…After the full‐text review, 64 studies were excluded further (overlapping data [ n = 2], other polymorphism loci [ n = 3], reviews [ n = 3], irrelevant studies [ n = 16], and biology studies [ n = 38]) (Figure 1). Finally, 16 studies involving 3786 patients and 5343 controls were included in this meta‐analysis (Bazina et al., 2015; Chehaibi et al., 2014; L. Huang et al., 2007; Lee et al., 2007, 2006; X. Li et al., 2016; Z. J. Liu et al., 2010; Lu et al., 2009; Shen & Ha, 2005; Sun, 2010; Tong et al., 2015, 2016; Wang et al., 2019; Wei et al., 2013; Yuan, 2008; Zafarmand et al., 2008). Of these, 10 case–control studies focused on rs1801282 C/G polymorphism (Bazina et al., 2015; L. Huang et al., 2007; Lee et al., 2006, 2007; X. Li et al., 2016; Shen & Ha, 2005; Tong et al., 2015, 2016; Wang et al., 2019; Zafarmand et al., 2008) and, seven case–control studies focused on rs3856806 C/T polymorphism (Chehaibi et al., 2014; Z. J. Liu et al., 2010; Lu et al., 2009; Sun, 2010; Wang et al., 2019; Wei et al., 2013; Yuan, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the full‐text review, 64 studies were excluded further (overlapping data [ n = 2], other polymorphism loci [ n = 3], reviews [ n = 3], irrelevant studies [ n = 16], and biology studies [ n = 38]) (Figure 1). Finally, 16 studies involving 3786 patients and 5343 controls were included in this meta‐analysis (Bazina et al., 2015; Chehaibi et al., 2014; L. Huang et al., 2007; Lee et al., 2007, 2006; X. Li et al., 2016; Z. J. Liu et al., 2010; Lu et al., 2009; Shen & Ha, 2005; Sun, 2010; Tong et al., 2015, 2016; Wang et al., 2019; Wei et al., 2013; Yuan, 2008; Zafarmand et al., 2008). Of these, 10 case–control studies focused on rs1801282 C/G polymorphism (Bazina et al., 2015; L. Huang et al., 2007; Lee et al., 2006, 2007; X. Li et al., 2016; Shen & Ha, 2005; Tong et al., 2015, 2016; Wang et al., 2019; Zafarmand et al., 2008) and, seven case–control studies focused on rs3856806 C/T polymorphism (Chehaibi et al., 2014; Z. J. Liu et al., 2010; Lu et al., 2009; Sun, 2010; Wang et al., 2019; Wei et al., 2013; Yuan, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 16 studies involving 3786 patients and 5343 controls were included in this meta-analysis (Bazina et al, 2015;Chehaibi et al, 2014;L. Huang et al, 2007;Lee et al, 2007Lee et al, , 2006X. Li et al, 2016;Z.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that multiple gene polymorphisms affect the occurrence of cerebral infarction. For example, CTSS gene [ 8 ] and PPARG2 gene [ 9 ] polymorphisms are associated with the occurrence of cerebral infarction in the Chinese population, and the ALDH2 gene polymorphism affects the collateral circulation and prognosis of cerebral infarction patients [ 10 ]. As the ligand for the growth hormone secretagogue receptor, the ghrelin gene promotes the release of growth hormone, thereby affecting various biological functions.…”
Section: Introductionmentioning
confidence: 99%